Mutant calreticulin‐expressing cells induce monocyte hyperreactivity through a paracrine mechanism. Issue 2 (February 2016) - Garbati, Michael R.; Welgan, Catherine A.; Landefeld, Sally H.; Newell, Laura F.; Agarwal, Anupriya; Dunlap, Jennifer B.; Chourasia, Tapan K.; Lee, Hyunjung; Elferich, Johannes; Traer, Elie; Rattray, Rogan; Cascio, Michael J.; et al.
Abstract : Mutations in the calreticulin gene ( CALR ) were recently identified in approximately 70–80% of patients with JAK2‐ V617F‐negative essential thrombocytosis and primary myelofibrosis. All frameshift mutations generate a recurring novel C‐terminus. Here we provide evidence that mutant calreticulin does not accumulate efficiently in cells and is abnormally enriched in the nucleus and extracellular space compared to wildtype calreticulin. The main determinant of these findings is the loss of the calcium‐binding and KDEL domains. Expression of type I mutant CALR in Ba/F3 cells confers minimal IL‐3‐independent growth. Interestingly, expression of type I and type II mutant CALR in a nonhematopoietic cell line does not directly activate JAK/STAT signaling compared to wildtype CALR and JAK2‐ V617F expression. These results led us to investigate paracrine mechanisms of JAK/STAT activation. Here we show that conditioned media from cells expressing type I mutant CALR exaggerate cytokine production from normal monocytes with or without treatment with a toll‐like receptor agonist. These effects are not dependent on the novel C‐terminus. These studies offer novel insights into the mechanism of JAK/STAT activation in patients with JAK2‐ V617F‐negative essential thrombocytosis and primary myelofibrosis. Am. J. Hematol. 91:211–219, 2016. © 2015 Wiley Periodicals, Inc.